Augmented reality mapping with AR markers for enhanced tourism experiences - Muhammad Kharibi, Nadiah; Toha, Siti Fauziah; Azmi, Nur Liyana; Idris, Ahmad Syahrin; Tokhi, Mohammad Osman (UTHM, 2024)
Implementation of augmented reality (AR) has increased productivity and provides real-time information and data to allow user to be aware of their surroundings. The objective of this research is to develop an augmented reality framework capable of overlaying real-time fruit identification results onto the physical environment in agricultural settings. The method approach to achieve this objective is using AR marker based and designed and developed using MATLAB. The study highlights that, regardless of some image quality limitations, complex feature detection algorithms like SURF and FAST can successfully mitigate the distortion and recovery processes. The results summarize that users of new augmented reality applications can now access helpful translation, mapping, and travel information.